Abordaje del monitoreo electrónico fetal intraparto alterado - Piloso Cedeño, Diana Alejandra (Machala : Universidad Técnica de Machala, 2022)
Electronic Fetal Intrapartum Monitoring was included within the obstetric care protocols, with the aim of evaluating the health of the fetus during labor, by evaluating the fetal heart rate, uterine contraction, acquisition, accelerations and decelerations of contractions uteri; allowing the professional to establish the most appropriate management to avoid fetal distress. Currently, the International Federation of Gynecology and Obstetrics, categorized the cardiotocographic registry as common, doubtful and pathogenic. Objective: To establish the altered intrapartum fetal monitoring approach to prevent fetal morbidity and mortality. Methodology: A bibliographical research of guides and articles was carried out based on data such as PubMed, Scielo, Web of Science and Scopus, with a publication time of less than 5 years. Conclusion: The pathological intrapartum fetal monitoring approach is performed through uterine resuscitation, starting with the lateralization of the pregnant woman, continuing with the administration of oxygen, correction of hypotension, and the suspension of the use of oxytocin or administration of emergency tocolysis. In the event that the cardiotocographic record does not stabilize, after implementing the aforementioned strategies, the pregnancy must be terminated either by vaginal delivery or cesarean section, in order to prevent neurological sequelae or fetal death.
El Monitoreo Electrónico Fetal Intraparto, se incluyó dentro de los protocolos de atención obstétrica, con el objetivo de valorar la salud del feto durante la labor de parto, mediante la evaluación de la frecuencia cardiaca fetal, contracción uterina, variabilidad, aceleraciones y desaceleraciones de contracciones uterinas; permitiendo al profesional establecer el manejo más adecuado para evitar el sufrimiento fetal. En la actualidad la Federación Internacional de Ginecología y Obstetricia, categorizó al registro cardiotocográfico como común, dudoso y patógeno. Objetivo: Establecer el abordaje del monitoreo fetal intraparto alterado, para prevenir la morbimortalidad fetal. Metodología: Se realizó una investigación bibliográfica de guías y artículos en base de datos como PubMed, Scielo, Web of Science y Scopus, con un tiempo de publicación menor a 5 años. Conclusión: El abordaje del monitoreo fetal intraparto patológico se realiza mediante la reanimación uterina, iniciando con la lateralización de la gestante, continuando con la administración de oxígeno, corrección de la hipotensión, y la suspender del uso de oxitocina o administración de tocolisis de emergencia. En el caso que el registro cardiotocográfico no se estabilice, luego de implementadas las estrategias antes indicadas, se debe terminar el embarazo ya sea por parto vaginal o cesárea, a fin de prevenir secuelas neurológicas o la muerte del feto.
Keywords: MONITOREO FETAL ELECTRÓNICO; REGISTRO CARDIOTOCOGRÁFICO; SUFRIMIENTO FETAL; COMPLICACIONES